ART THERAPY AS A MEANS OF CREATIVE DEVELOPMENT POTENTIAL OF YOUNG SCHOOL CHILDREN - Nazarova Zulaykho Turabovna (International Journal of Innovations in Engineering Research and Technology, 2021)
The article deals with the problem of the use of psychotherapy in working with children of primary school age that is relevant for modern psychology and the issues of using techniques and exercises of art therapy for the development of creative abilities. Examples of teaching methods aimed at the development of creative abilities are given.